The CC–NB–LRR protein BSR1 from Brachypodium confers resistance to Barley stripe mosaic virus in gramineous plants by recognising TGB1 movement protein. Issue 6 (19th September 2022) - Wu, Qiuhong; Cui, Yu; Jin, Xuejiao; Wang, Guoxin; Yan, Lijie; Zhong, Chenchen; Yu, Meihua; Li, Wenli; Wang, Yong; Wang, Ling; Wang, Hao; Dang, Chen; et al.
Summary: Although some nucleotide binding, leucine‐rich repeat immune receptor (NLR) proteins conferring resistance to specific viruses have been identified in dicot plants, NLR proteins involved in viral resistance have not been described in monocots. We have used map‐based cloning to isolate the CC‐NB‐LRR (CNL) Barley stripe mosaic virus (BSMV) resistance gene barley stripe resistance 1 ( BSR1 ) from Brachypodium distachyon Bd3‐1 inbred line. Stable BSR1 transgenic Brachypodium line Bd21‐3, barley (Golden Promise) and wheat (Kenong 199) plants developed resistance against BSMV ND18 strain. Allelic variation analyses indicated that BSR1 is present in several Brachypodium accessions collected from countries in the Middle East. Protein domain swaps revealed that the intact LRR domain and the C‐terminus of BSR1 are required for resistance. BSR1 interacts with the BSMV ND18 TGB1 protein in planta and shows temperature‐sensitive antiviral resistance. The R 390 and T 392 residues of TGB1ND (ND18 strain) and the G 196 and K 197 residues within the BSR1 P‐loop motif are key amino acids required for immune activation. BSR1 is the first cloned virus resistance gene encoding a typical CNL protein in monocots, highlighting the utility of the Brachypodium model for isolation and analysis of agronomically important genes for crop improvement.